Attractivity for Functional Volterra Integral Equations of Convolution Type - Lizama-Yanez, C (Elsevier B.V., 2016)
In this paper we investigate the existence of attractive and uniformly locally attractive solutions for a functional nonlinear integral equation with a general kernel. We use methods and techniques of fixed point theorems and properties of measure of noncompactness. We extend and generalize results obtained by other authors in the context of fractional functional differential equations. © 2016 Elsevier B.V. All rights reserved.